(untitled) (College of Basic Education Research Journal, 2025)
This research aims to establish and explore concept of code, a concept that Arabs have known since ancient times and called it cryptography", linked to signs and symbols. However, its modern concept is linked with approaches of linguist Ferdinand De Saussure in early twentieth century, to form cornerstone of semiotic thinking that represents a semantic interchange relationship between two elements. Research focused on initiation of novel (Desferal) by expatriate Iraqi novelist Nawzat Shamdin. Initiation is described as the condensed core of the text that is related to overall structure of work, and because initiation contradicts with its direct communicative language, it concealed many codes that current research attempted to deconstruct and identify their possible semantic dimensions, benefiting in particular - from procedural concepts of codes of event and symbol, which were established by French critic and philosopher Roland Barthes.